(untitled) (Boletin Médico de Postgrado, 2020)
Systemic Lupus Erythematosus (SLE) is a systemic disease of unknown etiology and with potentially fatal clinical forms; it can generate dysfunction of vital organs such as kidney, lung or nervous system. A cross-sectional descriptive field investigation was carried out to characterize clinically patients diagnosed with SLE admitted to the Hospital Pediátrico Dr. Agustín Zubillaga during the period 2009-2017. The sample included 19 cases, predominantly school children (42.1%) followed by preschoolers (31.6%). The average age was 10 years old, with a range between 6 months and 14 years. 10.6% of patients had a maternal family history of LES and rheumatoid arthritis. Fever and edema were the most frequent initial manifestations followed by arthralgia and headaches. Lupus nephritis occurred in 52.53% of the cases followed by cardiac alterations such as myocarditis and aortic stenosis (15.79%). Positive antinuclear antibodies was present in 45.45% of cases as well as hypocomplementemia in 22.73%. In conclusion, SLE is present in the pediatric population of our region and usually presents as a disease with severe systemic manifestations, mainly renal and myocardial, requiring hospitalization for timely remission treatment.